Bibliometric Analysis of Water Use and Irrigation in Agriculture - Loso Judijanto (Westscience Press, 2025)
This bibliometric analysis explores the evolving landscape of research on water use and irrigation in agriculture, with a focus on key themes such as soil carbon sequestration, groundwater depletion, nutrient management, and the water footprint. By examining the most-cited studies in the field, the study highlights the significant contributions of these topics to global food security and climate change mitigation. The analysis reveals the interconnectedness between environmental management, agricultural practices, and technological advancements, suggesting a need for integrated approaches in both policy and practice. While the study is based on citation data from indexed journals, it provides valuable insights for policymakers, practitioners, and researchers, emphasizing the importance of sustainable water management strategies. The findings contribute to theoretical frameworks by illustrating the complex relationships within agricultural sustainability, providing a foundation for future research in this crucial area.